Creatine phosphate preconditioning reduces ischemiareperfusion injury in isolated rat heart - L. A. Gadjieva; S. B. Bolevich; V. Jakovlevich; I. A. Omarov; H. A. Ordashev; M. K. Kartashova (Сеченовский вестник)
Aim. To study the effect of simultaneous administration of creatine phosphate immediately before ischemia on cardiodynamic parameters and biomarkers of oxidative stress in the coronary venous blood flow during retrograde perfusion in an isolated rat heart.Materials and methods. 20 Wistar albino rats were divided into 2 groups: group 1 (control) and group 2 (experimental), 10 rats per group. Cannulation and retrograde perfusion of aorta of an isolated rat heart with Krebs–Henseleit buffered solution by Landendorff was performed. Both groups underwent ischemia-reperfusion injury, which included global ischemia for 20 minutes followed by reperfusion for 30 minutes. The group 2 (experimental) was preconditioned with creatine phosphate at a dose of 0.2 mmol/l for 5 min before ischemia. We registered cardiodynamic parameters and indicators of oxidative stress at the point of stabilization, at the 1st and 30th minutes of reperfusion.Results. With the impact of creatine phosphate at the 30th minute of reperfusion in the group 2 in comparison with group 1, there was found an increase in the maximum and minimum speed of pressure elevation in the left ventricle (1.7 and 1.9 times, respectively), and of systolic and diastolic pressure in the left ventricle (1.5 and 1.6 times, respectively). Biomarkers of oxidative stress (lipid peroxidation index, nitrites, superoxide anion radical and hydrogen peroxide) were also statistically significantly lower in the group 2 after the 1st minute of reperfusion (by 1.2 times, by 1.4 times, by 2.8 times and 1.9 times, respectively), and after the 30th minute (1.3 times, 2.1 times, 1.9 times and 2.1 times, respectively).Conclusion. The administration of creatine phosphate into the coronary flow 5 minutes before the onset of ischemia has a protective effect on myocardial contractility. Reduction of oxidative stress and damage can be considered as a protective effect of creatine phosphate.